Urachal Adenocarcinoma: A Case Report with Key Imaging Findings and Radiologic-Pathologic Correlation - Willian Schmitt; Marta Baptista; Marco Ferreira; António Gomes; Ana Germano (Case Reports in Radiology)
Urachal pathologies are rare and can mimic numerous abdominal and pelvic diseases. Differential diagnosis of urachal anomalies can be narrowed down by proper assessment of lesion location, morphology, imaging findings, patient demographics, and clinical history. We report a case of a 60-year-old male, with a history of unintentional weight loss without associated symptoms, who was diagnosed with locally invasive urachal adenocarcinoma. With this article, we pretend to emphasize urachal adenocarcinoma clinical features along with its key imaging findings with radiologic-pathologic correlation.